PENGARUH INFLASI, IHSG DAN TINGKAT RETURN TERHADAP TOTAL NILAI AKTIVA BERSIH (NAB) PADA REKSADANA SYARIAH CAMPURAN YANG TERDAPAT DI OTORITAS JASA KEUANGAN PERIODE 2014-2018): PENGARUH INFLASI, IHSG DAN TINGKAT RETURN TERHADAP TOTAL NILAI AKTIVA BERSIH (NAB) PADA REKSADANA SYARIAH CAMPURAN YANG TERDAPAT DI OTORITAS JASA KEUANGAN PERIODE 2014-2018) - firzani firzani (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
ABSTRACT Net Asset Value (NAV) is a fair market value of the securities and other assets of mutual funds less liabilities (debt). NAV is one of the benchmarks in monitoring the results of a mutual fund. The purpose of this research is to analyze the effect of Inflation, IHSG and Return Rate on Net Asset Value (NAV) case studies at Mixed Sharia Mutual Funds in 2014-2018. This research is a quantitative research. The data collection technique used in this study was documentation technique. This study was used the Classical Assumption Test and Multiple Linear Regression Analysis. The results of this study indicated that inflation, IHSG and return rate have a significant effect on the NAV of Islamic mutual funds.